2016
DOI: 10.3847/1538-4357/833/1/29
|View full text |Cite
|
Sign up to set email alerts
|

Meterwavelength Single-Pulse Polarimetric Emission Survey. Ii. The Phenomenon of Drifting Subpulses

Abstract: A large sample of pulsars was observed as part of the Meterwavelength Single-pulse Polarimetric Emission Survey. We carried out a detailed fluctuation spectral analysis which revealed periodic features in 46% pulsars including 22 pulsars where drifting characteristics were reported for the first time. The pulsar population can be categorized into three distinct groups, pulsars which show systematic drift motion within the pulse window, the pulsars showing no systematic drift but periodic amplitude fluctuation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
170
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 77 publications
(190 citation statements)
references
References 56 publications
17
170
2
1
Order By: Relevance
“…Further observations at 300 MHz by Weltevrede et al (2007) revealed two P 3 values of 4.8±0.1 and 4.7±0.1 periods which were not possible to separate between the two components due to the sensitivity of their observations. Moreover, Basu et al (2016) have confirmed the 4.7±0.6 periods feature at 325 MHz and the 4.8±0.6 periods feature at 610 MHz. Here, we report its detailed behavior at 625 MHz with longer observations in contrast to Basu et al (2016).…”
Section: Introductionsupporting
confidence: 59%
See 4 more Smart Citations
“…Further observations at 300 MHz by Weltevrede et al (2007) revealed two P 3 values of 4.8±0.1 and 4.7±0.1 periods which were not possible to separate between the two components due to the sensitivity of their observations. Moreover, Basu et al (2016) have confirmed the 4.7±0.6 periods feature at 325 MHz and the 4.8±0.6 periods feature at 610 MHz. Here, we report its detailed behavior at 625 MHz with longer observations in contrast to Basu et al (2016).…”
Section: Introductionsupporting
confidence: 59%
“…Moreover, Basu et al (2016) have confirmed the 4.7±0.6 periods feature at 325 MHz and the 4.8±0.6 periods feature at 610 MHz. Here, we report its detailed behavior at 625 MHz with longer observations in contrast to Basu et al (2016). PSR J1840−0840 was discovered during the recent searches conducted from the Parkes telescope (Lorimer et al 2006).…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations